Advances in Industrial and Engineering Chemistry - Kim, Eunjoo; Lee, Sangho; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
Advances in Industrial and Engineering Chemistry (AIEC) is a leading journal that bridges the gap between scientific advancements and practical industrial applications across chemistry, materials, energy, bio, and environmental fields. Focused on all aspects of materials chemistry, AIEC serves as a multidisciplinary platform for impactful discussions that advance industrial sectors through novel discoveries and technologies. The journal provides authors with rigorous peer review, prompt decisions, and high visibility. The editors welcome original submissions that have not been published or are not under consideration elsewhere, including comprehensive research articles, short communications, notes, and reviews. AIEC particularly emphasizes the following areas: Energy Materials and Sustainable Energy Solutions: Topics include materials development and technological innovations for clean energy, such as renewable energy, energy storage and conversion, catalysis, fuel cells, secondary batteries, and hydrogen production. The journal prioritizes research on high-efficiency, low-cost energy storage systems, COb2 (Breduction technologies, and advanced materials to enhance the sustainability of fuels. Biomaterials and Bioenergy: This section covers sustainable bioenergy research, such as biomass, biofuels, and biorefineries, alongside bio-based materials, bioactive materials, medical materials, and biomimetic processes. AIEC aims to present diverse approaches to building a sustainable bioeconomy. Advanced Materials and Process Development: AIEC focuses on the design, synthesis, and characterization of advanced materials, including nanomaterials, porous materials, catalysts, and composites, essential for industrial applications. Research on material process development with considerations for industrial scalability and sustainability is also included. Eco-Friendly Chemical Processes: The journal promotes research related to environmental protection, such as waste reduction, water and air purification, and the development of sustainable chemical processes. Innovations in chemical processes and material development that contribute to energy savings and pollution prevention are covered. AI-Driven Convergence for Industrial Innovation: AIEC explores innovative industrial solutions that integrate cutting-edge technologies, such as AI, big data, and smart manufacturing. Topics include AI-enabled material design and optimization, big data-driven process improvement, and the development of smart manufacturing systems that align with sustainability goals. The journal seeks research that bridges the gap between the Fourth Industrial Revolution and industrial applications, fostering collaboration for transformative advancements. AIEC considers the applicability of all research, aiming to propose new paradigms for a sustainable future through collaboration and integration between academia and industry. AIEC particularly seeks groundbreaking achievements and novel solutions in the energy and bio sectors to drive industrial progress.s
Keywords: Chemistry, Technical; Chemical engineering; Industrial Chemistry; Chemical Engineering